2015
DOI: 10.1016/j.drugalcdep.2015.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a brief intervention to reduce the negative consequences of drug misuse among adult emergency department patients

Abstract: Objectives Determine if a brief intervention (BI) reduces the negative consequences of drug use/misuse among adult emergency department (ED) patients, and identify patients more likely to benefit from the BI. Methods This randomized, controlled trial enrolled 1,026 18–64 year-old ED patients whose drug misuse indicated a needed for a BI. Differences in total Inventory of Drug Use Consequences (InDUC) scores between the treatment (BI) and control arms (no BI) were assessed every 90 days over a one-year period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Drug‐focused SBIRTs delivered in primary care settings have mixed results. While some studies have not been shown to affect drug use significantly , a recent study of a drug‐focused, primary care‐delivered SBIRT found a significant decrease in the use of psychoactive drug use .…”
Section: Introductionmentioning
confidence: 98%
“…Drug‐focused SBIRTs delivered in primary care settings have mixed results. While some studies have not been shown to affect drug use significantly , a recent study of a drug‐focused, primary care‐delivered SBIRT found a significant decrease in the use of psychoactive drug use .…”
Section: Introductionmentioning
confidence: 98%
“…There have been numerous studies in the use of naloxone, both in the community and in the ED and its effectiveness in the reversal of respiratory depression [15][16][17][18] but that is only the fi rst step in addressing major harm from opioid addiction. Additionally, there have been a few studies that show brief intervention/ counseling of patients who self-report opioid addiction or misuse in the ED resulting in the reduction of opioid overdose risk behaviors [19][20][21]…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of SBIRT in health‐care settings, including the ED, however, has been mixed. Prior studies have supported the efficacy of alcohol brief interventions (BI) , although BIs targeting drug use have yielded inconsistent results and the inclusion of boosters has shown no effect . Further, the impact of alcohol and drug BIs on comorbid mental health problems (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol and drug misuse quadruple the risk of emergency department (ED) injury-related admissions world-wide [1,2]. Thus, the ED provides an invaluable setting for use have yielded inconsistent results [6][7][8][9][10][11] and the inclusion of boosters has shown no effect [12,13]. Further, the impact of alcohol and drug BIs on comorbid mental health problems (e.g.…”
Section: Introductionmentioning
confidence: 99%